KOMPETENSI KEPRIBADIAN GURU DALAM PEMBENTUKAN KARAKTER ISLAMI SISWA MTs MIDANUTTA’LIM MAYANGAN JOGOROTO JOMBANG - Elawati; Qurrotul Ainiyah; Nurul Lailiyah (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2021)
The teacher is an important component in forming the Islamic character of students. Because the teacher is the benchmark for achieving educational goals. Teachers who specifically focus on morals and character education for students are Akidah Akhlak teachers. The Akidah Akhlak teacher at MTs Midanutta'lim Mayangan Jogoroto Jombang, seen from his personality, is a person who is highly respected by other teachers and students. So that the personality displayed by the Akidah Akhlak teacher is expected to form the Islamic character of students at MTs Midanutta'lim Mayangan Jogoroto Jombang. Based on the above background, this research can be formulated as follows: To describe the teacher's personality competence in the formation of Islamic character of students at MTs Midanutta'lim Mayangan Jogoroto Jombang and to describe the Islamic character of Students at MTs Midanutta'lim Mayangan Jogoroto Jombang. This research uses qualitative or naturalistic methods because it is carried out in natural conditions. Qualitative research methods are research methods used to examine the condition of natural objects, where the researcher is the key instrument, the data collection technique is done by triangulation (combined), data analysis is inductive, and the results of qualitative research emphasize the meaning more than generalization. The Akidah Akhlak teacher at MTs Midanutta'lim Mayangan Jogoroto Jombang displays the teacher's personality competence in the form of exemplary so that it can become uswah or an example for students. Then the discipline by attending the madrasa on time, the religious attitude that is also displayed by Akidah Akhlak teachers through accompanying students when habituation is carried out routinely at the madrasah, and the attitude of authority displayed by Akidah Akhlak teachers through advice given to students when doing offense. The Islamic character of students that is formed is that students display a disciplined attitude, religious attitude and honest attitude.